The Technological Introject : Friedrich Kittler between Implementation and the Incalculable - Pfannkuchen, Antje; Champlin, Jeffrey; Zechner, Dominik; Reisoglu, Mert Bahadir; Weber, Samuel; Weber, Elisabeth; Dotzler, Bernhard; Gumbrecht, Hans Ulrich; Campe, Rüdiger; Ronell, Avital (Book collections on Project MUSE., 2018)
This essay collection further familiarizes the English-speaking world with the work of late German media scholar Friedrich Kittler. It features well-established and emergent scholars who present investigations that traverse all of Kittler's major phases, from early studies of German romanticism to his recent volumes on ancient Greece.